Impact of mobile services on business development and e-commerce - Liebana, Francisco, 1976-; Kalinic-Cabanillas, Zoran, 1971-; Luna, Iviane Ramos de, 1964- (Advances in electronic commerce series., 2020)
"This book examines the importance of mobile services in business development, including its advantages and possible disadvantages. It also explores links between economics, finance, marketing, consumer behavior, and computer science and information technology"--